Pengaruh Sludge dan Zeolit Terhadap Pertumbuhan Bibit Tanaman Karet (Hevea brasiliensis Muell Arg.) Stum Mini - Petrus Sihombing; Hapsoh Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was conducted on experimental farm of the Faculty of Agriculture, Universitas Riau, Pekanbaru Campus Binawidya Km 12.5 from February until May 2016. This trial uses completely randomized design (CRD) factorial and 3 replications. The first factor was zeolites consists of 3 levels (0, 50 and 100 g/plant) and the second factor was sludge consists of 4 levels (0, 50, 100 and 150 g/plant). The experiment data were analyzed statistically with Anova and DNMRT 5%. The parameters those observed: shoots height, in the number of leaves, upper trunk circumference, root volume, shoot to root ratio. Results indicate giving sludge and zeolites influential in increasing the length of shoots, in the number of leaves and volume root, except upper trunk circumference and ratio header root. Giving sludge dose of 100 g/ plant and zeolite dose of 100 g/ plant increase 27,83 cm shoot length, number of leaves 18,00 strands, upper trunk circumference 0,37 cm and 1,64 ratio root header from the age of 3 months to 7 months. Giving sludge dose of 150 g/ plant and zeolite dose of 100 g/ plant increase volume root 96.67 ml of 3 months to 7 months. Keywords:Rubber Seedling, Mini Stumps, Sludge, Zeolites